The Influence of Cognitive Factor and Technology Dimension on Behavioral Intention and Its Impact on Actual Behavior in Digital Banking: Evidence from Bank Jatim Kediri City - Angga Rizka Lidiawan; Nur Laely; Ana Komari; Djunaedi Djunaedi (Electronic Journal of Education, Social Economics and Technology, 2026)
As a leading regional development bank, Bank Jatim continues to strengthen its reputation through digital transformation initiatives, numerous national awards, asset growth reaching IDR 118.15 trillion (16.71% YoY), and support for regional digitalization (P2DD) and inclusive MSME development. Financial performance during 2016–2020 demonstrated significant growth, with assets increasing from IDR 43 trillion to IDR 83 trillion (±94%), third-party funds increasing by approximately 109%, and net profit growing by around 45%, reflecting financial stability and enhanced customer trust. This study aims to analyze the influence of Cognitive Factor and Technology Dimension on Behavioral Intention and its implications for Actual Behavior in digital banking usage among customers of Bank Jatim Kediri City. Using an explanatory quantitative approach with SEM-PLS and 173 respondents, the findings reveal that Cognitive Factor has the most dominant direct effect on Actual Behavior (β = 0.544; p 0.001; f² = 0.603), followed by Technology Dimension (β = 0.381; p 0.001; f² = 0.221). Behavioral Intention does not significantly affect Actual Behavior (β = 0.032; p = 0.645), indicating that it does not function as a mediator. The model demonstrates good fit (SRMR = 0.077; NFI = 0.838) and predictive relevance (Q² = 0.528). Theoretically, this study contributes by demonstrating that in the context of regional banking, trust and perceived risk play a more decisive role in shaping actual behavior than intention as a mediating variable. Practically, the findings recommend strategies focused on strengthening trust, enhancing digital security, providing assisted onboarding, and optimizing user experience to accelerate digital banking adoption